Chapter 3 Is there a glass ceiling or can racial and ethnic barriers be overcome? A study on leadership positions in professional Belgian football among African coaches - Heim, Chris (Routledge Critical Perspectives on Equality and Social Justice in Sport and Leisure, 2020)
In recent years there has been a steady increase in the racial and ethnic diversity of the playing workforce in many sports around the world. However, there has been a minimal throughput of racial and ethnic minorities into coaching and leadership positions. This book brings together leading researchers from around the world to examine key questions around 'race', ethnicity and racism in sports coaching. The book focuses specifically on the ways in which 'race', ethnicity and racism operate, and how they are experienced and addressed (or not) within the socio-cultural sphere of sports coaching. Theoretically informed and empirically grounded, it examines macro- (societal), meso- (organisational), and micro- (individual) level barriers to racial and ethnic diversity as well as the positive action initiatives designed to help overcome them. Featuring multi-disciplinary perspectives, the book is arranged into three thematic sections, addressing the central topics of representation and racialised barriers in sports coaching; racialised identities, diversity and intersectionality in sports coaching; and formalised racial equality interventions in sports coaching. Including case studies from across North America, Europe and Australasia, 'Race', Ethnicity and Racism in Sports Coaching is essential reading for students, academics and practitioners with a critical interest in the sociology of sport, sport coaching, sport management, sport development, and 'race' and ethnicity studies.